2016
DOI: 10.1002/smll.201601542
|View full text |Cite
|
Sign up to set email alerts
|

Click Synthesis, Aggregation‐Induced Emission and Chirality, Circularly Polarized Luminescence, and Helical Self‐Assembly of a Leucine‐Containing Silole

Abstract: By introducing chiral leucine pendants to silole scaffold, leucine-containing silole (Silole-Leu) is synthesized and it is endowed with not only aggregation-induced emission and circular dichroism, but excellent chiral polarized luminescence as well. Silole-Leu also has the capacity to self-assemble into nano/micro helical luminescent fibers and the dimension of the fibers can be tuned by adjusting the ratio and volume of mixed solvents for evaporation as revealed by atomic force microscope, scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Another method to develop CPL‐active materials is the introduction of chiral pendants into aggregation‐induced emissive molecules . A chiral silole derivative ( 208 ) with leucine‐containing attachments exhibited almost weak emission in the good solvent solution, whereas a significant enhancement in luminescent intensity was observed with increasing the ratios of poor solvent . The CPL measurement showed that the gradual addition of poor solvent induced the aggregation of leucine‐containing silole and produced helical fibers, which exhibited a strong negative CPL signal with the g lum of about −0.016.…”
Section: Supramoleculesmentioning
confidence: 99%
“…Another method to develop CPL‐active materials is the introduction of chiral pendants into aggregation‐induced emissive molecules . A chiral silole derivative ( 208 ) with leucine‐containing attachments exhibited almost weak emission in the good solvent solution, whereas a significant enhancement in luminescent intensity was observed with increasing the ratios of poor solvent . The CPL measurement showed that the gradual addition of poor solvent induced the aggregation of leucine‐containing silole and produced helical fibers, which exhibited a strong negative CPL signal with the g lum of about −0.016.…”
Section: Supramoleculesmentioning
confidence: 99%
“…[34] By using the same luminophor and synthetic procedure, we then prepared two chiral silole derivatives 2 and 3 with l-valine-and l-leucine-containing attachments,r espectively. [35,36] To expand the system,t he thiourea-linked chiral silole derivative 4 was synthesized by incorporatingc hiral phenylethanamine moieties onto the tetraphenylsilole unit. [37] Consideringt hat some achiral p-conjugated molecules can form helical assemblies through asymmetric packing of achiral building blocks, [38][39][40] we also prepared an achiral silole compound, hexaphenylsilole (HPS, 5)f or comparison.…”
Section: Silole Derivativesmentioning
confidence: 99%
“…SEMi mage of the helicalfibers formed by 3 uponthe evaporation of its DCE solution. Concentration:1 00 mm.Reprinted with permission from ref [36]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Organic molecules have the merits to offer infinite materials of different chemical and physical properties by varying its chemical structures and functionalities. On the one hand, development of chiral small organic molecules is growing for tunable wavelengths, high quantum yields, excellent processability, and easy derivatization . Biaryls compounds with axial chirality have been investigated extensively for CPL‐active materials .…”
Section: Amplification Of Cpl Through Tta‐based Photon Upconversionmentioning
confidence: 99%